International Outsourcing: a process approach to the apparel industry - Alves Moreira, Maria Rosario; R.S. Andrade, Sofia; S.A. Sousa, Paulo (Review of Business Management, 2015)
Objective – The purpose of this paper is to build a framework for an international outsourcing process in the apparel industry that can serve to support managerial decisions and actions regarding outsourcing choices and implementation. Design/methodology/approach – We developed of a straightforward and flexible framework describing the main stages of the international outsourcing process and its main activities with application in the context of the apparel industry. A case study approach was adopted with primary data collected through in-depth interviews and secondary data aggregated from company reports and documents. Theoretical foundation – Some research gaps in the outsourcing literature and most specifically on the matter of international outsourcing were identified by Hatonen and Eriksson (2009) and Kakabadse and Kakabadse (2000), among others. Specifically, these authors claim that there is not enough research on developing and offering decision models, tools or guidelines to support managerial decisions with the appropriate empirical evidence. This study aims to address this gap. Findings – We found that the international outsourcing process can be described using the proposed framework. Apparel companies can use this framework to support and supervise international outsourcing processes. Practical implications – This study provides a simple model that can help companies in the apparel industry to enhance their outsourcing activities and operations, and also contributes to a broader academic understanding of the matter.